The Effects of Journalism on Digital News Systems: Academic Perspectives - Bayu Aji Pamungkas; Fitratul Husna; Surya Mahmuda (Sociometry Journal of Social Science, Art and Humanity, 2021)
The study's purpose is to find the impact of developments in the era of digital news according to the lecturer's view and the effects of digitalization on the news system. Who researched this article with the perspective of postpositivist methods qualitative in-depth interviews to informants who included professors of Journalism category of the effect of digital news, additional information in the get through articles, journals, and books that refer to the theme associated with the research. The result of this research is that the Development of Information and Communication Technology has spread in all fields, especially in Journalism media and Citizen Journalism, where everyone can disseminate all the information without having a background in the field of Journalism. This phenomenon resulted in the widespread dissemination of news hoaxes. Journalism also develops multimedia refers to the technique of percentage or news presentation, which focuses on the writing and visual images, both moving and still, turned on.